Pedestrian flow and environmental pollutants distribution in apartment stairwells: Strategies for sustainable indoor environment management - Xiaodong Wang; Yang Lv; Liu Tang (Sustainable Futures)
This study explores pedestrian flow and indoor pollutant distribution in apartment stairwells, a key but underexplored vertical space in high-density housing. Calibrated air quality sensors were used to monitor PM2.5, PM10, total volatile organic compounds (TVOC), formaldehyde, ozone, carbon monoxide, and noise, while infrared pedestrian counters recorded pedestrian flow. Results showed that peak pedestrian flow accounted for 62.0 % of total usage, concentrated mainly during morning, noon, and evening rush hours. Stairwell use declined by approximately 50 % with each additional floor. Aligning elevator stop strategies with residents’ stairwell usage patterns can help improve operational efficiency and reduce energy consumption. Environmental monitoring revealed that TVOC and noise levels frequently exceeded recommended indoor standards during peak periods. TVOC concentrations reached as high as 4.6 mg/m³ on the 3rd floor, exceeding threshold levels for 70.8 % of the 24-hour cycle. A strong correlation was observed between indoor and outdoor ozone concentrations, with indoor levels remaining below 49 % of the outdoor maximum. Correlation analysis revealed that PM2.5 and PM10 levels were mainly influenced by outdoor factors, while noise emerged as a strong predictor of TVOC fluctuations. Additionally, reducing TVOC levels was associated with suppressed ozone formation and limited inter-floor diffusion, offering insights for targeted pollutant control. By integrating behavioral patterns with environmental data, this study proposes practical strategies for optimizing elevator scheduling and mitigating pollutant exposure in stairwells. These strategies not only enhance the environmental sustainability of stairwells as transitional spaces but also reduce residents’ exposure to indoor pollutants and promote environmental health equity.